Two-shift operation mode can improve the efficiency and comfort of flexible ureteroscopic holmium laser lithotripsy for the treatment of renal calculi larger than 1.5cm - Hui,Sun (2019)
ABSTRACT Purpose: To compare two-shift operation mode and single player mode different impact on surgical results and operator comfort in flexible ureteroscopic holmium laser lithotripsy for renal calculi larger than 1.5cm. Materials and Methods: From december 2017 to december 2018, 92 patients with renal calculi admitted to Qilu Hospital and were treated through flexible ureteroscopy. They were randomized in two-shift group (n=50) and single player group (n=42). The operative time, blood loss, hospitalization stay after operation, residual fragments (≥4mm) rate, fragmentation speed, postoperative complications and operator's fatigue score were compared. Results: There was no significant difference between two groups regarding age, gender, illness side, stone size, blood loss, operative time, postoperative hospitalization stay, complications, etc (p >0.05). The fragmentation speed was 44.5±20.0mm3/min in two-shift group compared with 34.2±17.3mm3/min in single player group (p=0.037). Residual fragments (≥4mm) rate after first surgery was 18% in two-shift group, while the residual fragments (≥4mm) rate was 40.5% after first surgery in single player group (p=0.017). The total fatigue score of two-shift group was 8.4 compared to 29.9 in single player group (p <0.001). Conclusion: In flexible ureteroscopic holmium laser lithotripsy for the treatment of renal calculi larger than 1.5cm, two-shift operation mode can raise the fragmentation speed and stone clearance rate, as well as significantly lower operator's fatigue level and improve operator's comfort.